Growth of exercise science in the United States since 2002: A secondary data analysis - Nuzzo, J. L. (Quest, 2020)
Anecdotally, exercise science has experienced substantial growth in the past 20 years. Limited descriptions of this growth exist. In the current report, the author describes the number of exercise science bachelor`s, master`s, and doctoral degrees awarded in the United States from 2002-03 to 2016-17. Data were retrieved from the National Center for Education Statistics and summarized by academic major, year, sex, and relative growth over time. In 2002-03, 5,248 bachelor`s degrees were awarded in exercise science (58% females; 0.39% of all bachelor`s degrees awarded; rank of 53 of 843 majors). In 2016-17, 28,587 bachelor`s degrees were awarded in exercise science (55% females; 1.46% of all bachelor`s degrees awarded; rank of 14 of 1,062 majors). From 2002-03 to 2016-17, exercise science experienced the fourth largest growth (445%) in bachelor`s degrees awarded. Exercise science is a fast-growing academic major in the United States. Potential for market oversupply of exercise science graduates warrants discussion among higher education and professional organizations.